2011
DOI: 10.1016/j.ridd.2011.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Work stress, burnout, and social and personal resources among direct care workers

Abstract: Work stress is endemic among direct care workers (DCWs) who serve people with intellectual and developmental disabilities. Social resources, such as work social support, and personal resources, such as an internal locus of control, may help DCWs perceive work overload and other work-related stressors as less threatening and galvanize them to cope more effectively to prevent burnout. However, little is known about what resources are effective for coping with what types of work stress. Thus, we examined how work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 23 publications
7
86
0
1
Order By: Relevance
“…Experiences at work, whether physical, emotional or social in nature, affect the person; moreover, these experiences "spill over" into non-work life domains (Danna & Griffin, 1999). This issue may be exacerbated among those working in mentally and emotionally demanding work, such as in mental health services (Ben-Zur & Michael, 2007;Cooper & Cartwright, 1994;Elliot & Guy, 1993;Gray-Stanley & Muramatsu, 2011;Lloyd, King, & Chenoweth, 2002;Moore & Cooper, 1996;Totterdell, Wood, & Wall, 2006).…”
Section: The Workplace Context: Stress and Its Impacts On Job Incumbentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiences at work, whether physical, emotional or social in nature, affect the person; moreover, these experiences "spill over" into non-work life domains (Danna & Griffin, 1999). This issue may be exacerbated among those working in mentally and emotionally demanding work, such as in mental health services (Ben-Zur & Michael, 2007;Cooper & Cartwright, 1994;Elliot & Guy, 1993;Gray-Stanley & Muramatsu, 2011;Lloyd, King, & Chenoweth, 2002;Moore & Cooper, 1996;Totterdell, Wood, & Wall, 2006).…”
Section: The Workplace Context: Stress and Its Impacts On Job Incumbentsmentioning
confidence: 99%
“…Indeed, stress and burnout and their impacts have been well documented among mental health professional groups including nurses, social workers and psychotherapists (Ben-Zur & Michael, 2007;Demerouti, Baker, Nachreiner, & Schaufeli, 2001;Gray-Stanley & Muramatsu, 2011;Harvey & Burns, 1994;Lloyd et al, 2002;Pines, 2008;Thoresen, Kaplan, Barsky, Warren, & De Chermont, 2003;Webster & Bergman, 1999;Welbourne et al, 2006;Winstanley & Whittinton, 2002). Such research has indicated that mental health workers appear to experience higher levels than do general community members of emotional distress, generalised anxiety, depression and burnout rates.…”
Section: The Workplace Context: Stress and Its Impacts On Job Incumbentsmentioning
confidence: 99%
See 3 more Smart Citations